Comparison of three device generations of the StepWatch Activity Monitor: analysis of model version agreement in pediatric and adult independent ambulators - Stevens, Wilshaw R.; Barrett, Cody; Jeans, Kelly A. (Frontiers in Sports and Active Living, 2024)
Purpose Devices such as the StepWatch Activity Monitor (SAM) have been available for 20 years and have been shown to accurately measure ambulatory activity. This study aimed to evaluate the agreement among the three generations of the StepWatch Activity Monitor (SW3, SW4, and SW5) with respect to stride count. Methods A total of 36 participants (age range, 6–55 years) participated in this institutional review board-approved study. The participants concurrently wore three different SAM model devices on the same leg and performed a 6-min walk test (6MWT). A research staff member of the laboratory manually counted the number of strides for the first 2 min of the test (2MWT). Agreement among the device models was evaluated by calculating ANOVAs and interclass correlation coefficients (ICCs) and creating Bland–Altman plots. Results There was no significant difference among the model versions during the 6MWT and 2MWT (p > 0.05). The ICC for the total stride count was 0.993 (95% CI = 0.988–0.996) during the 2MWT and 0.992 (95% CI = 0.986–0.996) during the 6MWT. There was a near-perfect agreement (ICC ≥ 0.990) of each model version to the manually counted strides during the 2MWT. The systematic bias of all three SAM model versions was <1 step. Conclusions The results from the present study demonstrate that the stride counts among all three devices are comparable and relative to the manual stride count. All three SAM model versions had an ICC of >0.90. Researchers can safely incorporate historical data from previous SAM model versions with newer data collected with the latest SAM model version.